International Law Moot Court Competition 1994 World Championship Jessup Cup Round National University of Singapore v. University of Melbourne - Jessup, Philip C. (Philip Caryl), 1897-; American Society of International Law.; International Law Students Association (Washington, D.C. : International Law Students Association, 1994)
The program discuss the case of concerning the granting of refugee status: Freedonia v. Balboa.
Keywords: Refugees -- Legal status, laws, etc